Prevalence and Distribution of Thalassemia Trait Screening - Nailil Husna; Imanuel Sanka; Ahmad Al Arif; Chintya Putri; Elory Leonard; Niken Satuti Nur Handayani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
Thalassemia is an inherited disorder of autosomal recessive gene caused by decrease or absent production of one or two type of globin chain. This disorder will affect the quality and quantity of blood production. In Indonesia, thalassemia is not concerned as urgency, although it lies in thalassemia belt area. Thalassemia is classified according to the particular globin chain which affected such as α-thalassemia and β-thalassemia. Besides thalassemia, there are variant hemoglobinopathy called HbE. The aim of this study was to assess the prevalence of thalassemia carriers among the volunteer of screening in province DI Yogyakarta from 2012 until 2015. The thalassemia carrier screening was conducted by collaborating with Indonesian Association of Parents of Children with Thalassemia (POPTI) Yogyakarta. The hematological measurement and High-Performance Liquid Chromatography (HPLC) were performed on Prodia Laboratory Yogyakarta. The analysis of carriers prevalence was conducted in Laboratory of Genetics and Breeding, Faculty of Biology, Universitas Gadjah Mada. From 241 volunteers, we found 44 volunteers was diagnosed as β-thalassemia carrier, 30 volunteers as α-thalassemia carrier as well as HbE disorder carrier, and 1 volunteer was diagnosed as α-β-thalassemia carrier. The number of thalassemia carrier shows no significant difference each year. The prevalence of thalassemia carrier was high, even though the distribution is limited by the location where the screening took place.Keywords : Thalassemia trait screening - α-thalassemia - β-thalassemia – HbE – HPLC